Development and validation of a questionnaire to assess knowledge, attitude, practices, and concerns regarding COVID-19 vaccination among the general population. Issue 3 (May 2021) - Kumari, Archana; Ranjan, Piyush; Chopra, Sakshi; Kaur, Divjyot; Upadhyay, Ashish Datt; Kaur, Tanveer; Bhattacharyya, Arunangshu; Arora, Mehak; Gupta, Hardik; Thrinath, Arnav; Prakash, Bindu; Vikram, Naval K.
Abstract: Background and aims: There seems to be hesitation in the general population in accepting COVID 19 vaccine because of associated myths and/or misinformation. This study is dedicated to develop and validate a tool to interpret vaccine acceptance and/or hesitancy by assessing the knowledge, attitude, practices, and concerns regarding the COVID vaccine. Material and methods: Mixed methods study design was used. In phase 1, the questionnaire was developed through literature review, focus group discussion, expert evaluation, and pre-testing. In phase 2, the validity of the questionnaire was obtained by conducting a cross-sectional survey on 201 participants. The construct validity was established via principal component analysis. Cronbach's alpha value was used to assess the reliability of the questionnaire. Results: The 39-item questionnaire to assess the knowledge, attitude, practices, and concerns regarding the COVID-19 vaccine was developed. The Cronbach's alpha value of the questionnaire was 0.86 suggesting a good internal consistency. Conclusion: The developed tool is valid to assess the knowledge, attitude, practices and concerns regarding the COVID-19 vaccine acceptance and/or hesitancy. It has the potential utility for healthcare workers and government authorities to further build vaccine literacy. Highlights: Crucial to determine people's knowledge, attitude, practices, and concerns regarding COVID-19 vaccine. Our validated tool assesses knowledge, attitude, practices, and concerns regarding the COVID-19 vaccine. Our tool will assist concerned authorities to work towards successful vaccination drive.